2023
DOI: 10.3390/polym15143066
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Effect on Ramie-Fiber-Reinforced Polymer Composite Plates: Water Uptake and Mechanical Properties

Abstract: Ramie-fiber-reinforced polymer composites (RFRP) have the advantages of low price and low energy consumption, but they have high hydrophilicity due to their special chemical composition. In order to study the effect of water absorption on the performance degradation of RFRP in a hydrothermal environment, the authors prepared RFRP sheets by compression molding. Manufactured composites were exposed to a hydrothermal environment with a temperature of 40 °C and a humidity of 50% RH, 85% RH and 98% RH to study the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The alkali process that was introduced caused the hydrogen bonds to break and the amorphous area to terminate [17]. The treatment may result in a decrease in non-cellulosic materials and an increase in the fibres surface area, which may raise the quantity of hydrophilic groups on the fibres surface [18]. The outcome showed that the alkali process's elimination of contaminants like lignin and hemicellulose considerably lowers the ramie fibres diameter and prevents defibrillation [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alkali process that was introduced caused the hydrogen bonds to break and the amorphous area to terminate [17]. The treatment may result in a decrease in non-cellulosic materials and an increase in the fibres surface area, which may raise the quantity of hydrophilic groups on the fibres surface [18]. The outcome showed that the alkali process's elimination of contaminants like lignin and hemicellulose considerably lowers the ramie fibres diameter and prevents defibrillation [19].…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that ramie fibres have potent hydrophilic qualities [20]. The hydrophilic group on the surface of ramie fibres ameliorates when they were treated with increasing concentrations of alkali, which enhanced the fibre's ability to absorb water [18]. However, the performance of sodium hydroxide's dispersion stability was diminished when the concentration raised to 15%.…”
Section: Resultsmentioning
confidence: 99%